The Blessing of Cash - Franz Seitz; Malte Krueger (Deutsche Bundesbank, 2017)
This study investigates the benefits of cash in a general context. First, we explicitly address the arguments of cash critics, who are calling for cash to be abolished altogether. Second, we show that cash plays a crucial role in the current two-tier banking system. Third, we are discussing a number of selected benefits of cash, inter alia its use in financial crisis and the provision of privacy. We conclude that the abolition of cash would have major drawbacks and could entail undesirable consequences.
Keywords: D12; D61; E41; G21; O33; 330; cash; payments; cash abolition; monetary policy